ANALISIS PENGARUH TINGKAT BUNGA KREDIT, DANA PIHAK KETIGA, DAN TINGKAT INFLASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SULAWESI SELATAN MELALUI PENYALURAN KREDIT - Viony Lencye Maembuna; Mauna Th. B. Maramis; Dennij Mandeij (Jurnal Riset Multidisiplin Edukasi, 2025)
Economic growth is the increase in the value of goods and services produced in a country over a certain period of time. This study aims to analyze the influence of credit interest rates, third-party funds, and inflation rates on economic growth in South Sulawesi Province through credit distribution. This study uses a quantitative approach with the path analysis method to analyze the relationship between independent variables and dependent variables through mediating variables. Secondary data used were obtained from Bank Indonesia (BI) and the Central Statistics Agency (BPS). The results of this study indicate that directly, credit interest rates, third-party funds, and inflation rates have a negative and insignificant relationship to economic growth in South Sulawesi Province. However, these three variables indirectly have a positive effect on economic growth through credit distribution. Credit distribution has a positive and insignificant relationship to economic growth, and acts as a moderating variable that strengthens the influence of independent variables on the dependent variable. In addition, simultaneously, credit interest rates, third-party funds, and inflation rates do not affect economic growth. Meanwhile, simultaneously, the Credit Interest Rate, Third Party Funds, and Inflation Rate have an effect on Credit Distribution, where each of these variables has a positive and significant relationship with Credit Distribution.